Engineering Pedagogy in the Context of Engineering Activity - V. G. Martynov; V. S. Sheinbaum (Высшее образование в России, 2022)
Engineering pedagogy is a professional activity that forms and develops the required future engineers’ competences with the help of appropriate pedagogical tools and technologies. It is essential that engineering graduates were productive, ready to actively participate in the innovative development of the chosen sphere. Ongoing development of engineering activity, its modernization, improvement, expansion into other areas of activity requires adjustment, updating goals, means and methodology of educational activity in general and engineering pedagogy in particular. Today engineering pedagogy should focus on the issues of a new ontology of engineering activity. The article aims to clarify ontological and methodological foundations of engineering activity, consider it as a multidimensional and multivariate system of division of labour, an open dynamic interdependent system. The article dwell on the conception of engineering designing, which has a property of recursiveness so that engineering activity may design itself. The authors argue that namely activity ontology should become the basis of the new methodology of engineering pedagogy, which creates the tools for training new generations of engineers by means of continuous professional education of university teaching staff.